Experimental study on compression properties and failure mechanism of 3D MWK carbon/epoxy composites at elevated temperatures. (25th July 2017) - Jiang, Nan; Li, Dian‐Sen; Yao, Qian‐qian; Duan, Hong‐wei; Ko, Frank
Abstract : The compressive behavior of the 3D MWK carbon/epoxy composites with two fiber architectures were performed in longitudinal and transverse directions at room and elevated temperatures. Macro‐fracture and SEM micrographs were examined to understand the deformation and failure mechanism of 3D MWK carbon/epoxy composites. The results show that the compression properties and failure patterns vary with the temperature, fiber architecture, and loading mode. The compressive stress–strain curves and properties are different in longitudinal and transverse directions. Meanwhile, the properties increase with the increase of fiber orientation angle and decrease significantly with the increase of temperature, especially after 75°C. Moreover, for longitudinal compression, material A [0°/90°/+45°/‐45°] exhibits shear brittle feature and that the delaminating failure at elevated temperatures, while material B[0°/0°/0°/0°] behaves multiple shear fracture at 45°. For transverse compression, material A shows delaminating fracture along 0°, 90°, +45°, −45° fiber layers and material B is the delaminating between 0° fiber layers. At elevated temperatures, the damage of matrix yielding, cracking, and interface debonding become prominent, the composite becomes more softened and attains plasticity. POLYM. COMPOS., 39:E1987–E1999, 2018. © 2018 Society of Plastics Engineers